Agensi dan Komodifikasi Permainan Tradisional pada Komunitas Kampoeng Dolanan Surabaya: Perspektif Pierre Bourdieu - Wildan Wahyudinata (YASIN, 2026)
Traditional games as a form of local wisdom in Indonesia are threatened with extinction due to the dominance of modern technology-based games and changing lifestyles in urban communities. This situation has encouraged the emergence of cultural agency communities that seek to prevent the disappearance of traditional games, including in major cities such as Surabaya through the Komunitas Kampoeng Dolanan. This study aimed to analyze the role of Komunitas Kampoeng Dolanan Surabaya as a cultural agency for the preservation of traditional games and simultaneously as an actor in cultural commodification within urban society. The research employed a qualitative method with a case study approach through field observations and in-depth interviews with the founder and other parties involved in the community. Data were analyzed using Pierre Bourdieu’s perspective, particularly the concepts of habitus, cultural capital, and field, as well as the concept of cultural commodification. The findings show that commodification practices in Kampoeng Dolanan originated from the founder’s personal habitus, which then developed into the community’s collective habitus and encouraged the formation of a cultural field that enables the production, distribution, and consumption of traditional games with economic value. The community has developed various creative divisions that manage the production of game equipment, educational activities, and culture-based services as sources of economic and social capital as well as a means of cultural preservation. The study concludes that cultural preservation and commodification are not always contradictory, but can instead operate simultaneously as a strategy for the sustainability of cultural communities. The implications of this research affirm that culture-based communities hold strategic potential for safeguarding local cultural heritage while empowering the community’s economy, provided they are managed reflectively and ethically.